Understanding property market operations from a dual institutional perspective: The case of Lagos, Nigeria. (November 2017) - Agboola, Alirat Olayinka; Scofield, David; Amidu, Abdul-Rasheed
Abstract: This paper examines the Nigeria Land Use Act and considers how provisions of the Act inform and influence traditional landholding systems, the operation of the commercial real estate market, and the activities of the "omo-onile." The research adopts a qualitative strategy and combines analysis of legal statute with in-depth, semi-structured interviews with market participants active in different capacities within the land and property markets of Lagos, Nigeria. The paper identifies a number of inconsistencies in the provisions of the Act and concludes that the recognition given to the traditional landholding system by the Act has not been effective in tackling informality and illegality in Lagos land and property markets. The paper provides insight into how informal institutions of norms, culture, and conventions of a real estate market characterize property ownership and affect transaction processes. This study shows how informal institutions may be used to circumvent formal institutions of a market when formal rights to property are poorly delineated and assigned. In these conditions market actors will incur higher transaction costs in the process of policing transactions and enforcing contractual agreements.